A Multipronged Approach in Targeting Clostridium difficile: Multiple Domain Selection for Aptamer Isolation - Arrabi, Amjad (My University, 2017)
Clostridium difficile, the causative agent of C. difficile infection (CDI), causes hundreds of thousands of hospital-acquired infections in the United States and Canada annually. Furthermore, the prevalence and severity of CDI has been on the rise in developed countries, especially with the appearance of “hypervirulent” strains. Detection of CDI is thus of great importance. Traditional detection methods can be time consuming or lack the desired sensitivity. On the other hand, aptamers pose great prospects as diagnostic and therapeutic agents. Aptamers are nucleic acid ligands with molecular recognition capabilities rivaling those of antibodies. They are obtained by a process of in vitro selection known as systematic evolution of ligands by exponential enrichment (SELEX). However, the current approach may result in aptamers that experience non-specific binding in complex or biological samples. Here, we propose a multiple domain selection (MDS) method for aptamer isolation. This method utilizes independent selections on separate components of a single target in order to obtain uniquely specific aptamers. The aptamers can then be unified into a heterobivalent construct able to recognize two sites on one target. We hypothesize the combined aptamer would result in greater affinity and specificity for the target, resulting in greatly increased aptamer utility in current and future applications. In the current study, we have cloned and purified full length C. difficile DnaK as well as the N-terminal domain (NTD) and C-terminal domain (CTD) of the protein. MDS was performed on each target and the resulting aptamers were combined into a heterobivalent construct. The construct resulted in an approximately 100-fold affinity increase relative to the single aptamer for DnaK, and could detect much smaller quantities of target. Although it experienced low level recognition of high concentrations of purified E. coli DnaK, there was no detectable non-specific binding in several biological samples.
Keywords: Aptamer; SELEX; Nucleic Acids; DNA; C. difficile; Multiple Domain Selection; MDS; DnaK; Hsp70